2022
DOI: 10.3389/fmolb.2022.828886
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Novel Prognostic Models for Immune-Related Genes in Osteosarcoma

Abstract: Immunotherapy has shown excellent therapeutic effects on various malignant tumors; however, to date, immunotherapy for osteosarcoma is still suboptimal. In this study, we performed comprehensive bioinformatic analysis of immune-related genes (IRGs) and tumor-infiltrating immune cells (TIICs). Datasets of differentially expressed IRGs were extracted from the GEO database (GSE16088). The functions and prognostic values of these differentially expressed IRGs were systematically investigated using a series of bioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…These results suggested that osteosarcoma in the high-risk group of DGPS can be classified as a cold tumor subgroup, i.e., with poorer immune infiltration and possibly poorer response to immunotherapy [ 52 , 53 ]. The expression of immune checkpoints LAG3, NRP1, CD40LG, C10orf54, CD86, CD48, CD274, HAVCR2, CD27, CTLA4, CD200R1, LAIR1, LGALS9, CD28, and PDCD1LG2 was significantly higher in the low-risk group than in the high-risk group, and it was previously confirmed in the literature that LAG3 [ 54 ], CD86 [ 55 ], HAVCR2 [ 56 ], CD27 [ 57 ], LAIR1 [ 58 ], and PDCD1LG2 [ 56 ] checkpoints play important roles in osteosarcoma cell therapy. These results suggested that these checkpoints could be potential targets for osteosarcoma therapy and that DGPS could provide a new criteria to guide osteosarcoma immunotherapy.…”
Section: Discussionmentioning
confidence: 64%
“…These results suggested that osteosarcoma in the high-risk group of DGPS can be classified as a cold tumor subgroup, i.e., with poorer immune infiltration and possibly poorer response to immunotherapy [ 52 , 53 ]. The expression of immune checkpoints LAG3, NRP1, CD40LG, C10orf54, CD86, CD48, CD274, HAVCR2, CD27, CTLA4, CD200R1, LAIR1, LGALS9, CD28, and PDCD1LG2 was significantly higher in the low-risk group than in the high-risk group, and it was previously confirmed in the literature that LAG3 [ 54 ], CD86 [ 55 ], HAVCR2 [ 56 ], CD27 [ 57 ], LAIR1 [ 58 ], and PDCD1LG2 [ 56 ] checkpoints play important roles in osteosarcoma cell therapy. These results suggested that these checkpoints could be potential targets for osteosarcoma therapy and that DGPS could provide a new criteria to guide osteosarcoma immunotherapy.…”
Section: Discussionmentioning
confidence: 64%
“…Several oncogenes, including SEMA4D and SEMA6D, have been involved in axon guidance in human osteosarcomas [ 18 ]. SEMA4D is one of the immune‐related genes (IRGs) used to generate clinical utility models [ 19 ]. These reports demonstrated that the enriched genes identified through our library screening might play an important role in osteosarcoma cisplatin resistance and our screening strategy efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Cisplatin is a key drug in osteosarcoma therapy. It has been reported that several genes or pathways contribute to cisplatin resistance [ 19 , 20 , 21 , 22 ]. In this study, we discovered that 78 genes might be responsible for cisplatin resistance using 143B osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR and WB were performed as described previously ( 18 ). RT-qPCR reagents such as AG RNAex Pro Reagent, SYBR Green Premix Pro Taq HS qPCR kit and the Evo M-MLV RT Premix kit were purchased from Accurate Biology.…”
Section: Methodsmentioning
confidence: 99%